2019
DOI: 10.3390/molecules24162992
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Salix babylonica L. and Their Antibacterial Activity Against Gram-Positive and Gram-Negative Animal Bacteria

Abstract: The principle of animal wellbeing, which states that animals should be free from pain, injury, and disease, is difficult to maintain, because microorganisms are most frequently found to be resistant or multi-resistant to drugs. The secondary metabolites of plants are an alternative for the treatment of these microorganisms. The aim of this work was to determine the antibacterial effect of Salix babylonica L. hydroalcoholic extract (SBHE) against Escherichia coli, Staphylococcus aureus and Listeria monocytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 28 publications
4
21
0
2
Order By: Relevance
“…Nevertheless, antibacterial activity was not detected for E. coli and S. aureus. It was determined that the antibacterial response seen in treatments CT2 and CR3 were bactericidal, since the relation between MIC and MBC is less than 4, in accordance with González-Alamilla et al, in 2019 [18].…”
Section: Antibacterial Activitysupporting
confidence: 76%
“…Nevertheless, antibacterial activity was not detected for E. coli and S. aureus. It was determined that the antibacterial response seen in treatments CT2 and CR3 were bactericidal, since the relation between MIC and MBC is less than 4, in accordance with González-Alamilla et al, in 2019 [18].…”
Section: Antibacterial Activitysupporting
confidence: 76%
“…Furthermore, Rivero-Pérez et al [ 49 ] determined the partial chemical composition of S. babylonica hydroalcoholic extract, finding phenolic compounds, coumarins, lactans, sterols, triterpenes, flavonols, flavonoids, saponins, and floratanins, as well as linalol, thymol, and carvacrol, which were identified using gas chromatography. González-Alamilla et al reported that the organic fraction of S. babylonica hydroalcoholic extract [ 27 ] contains the secondary metabolites with the highest antibacterial activity and determined that two flavonoids (luteolin and luteolin glucoside) are responsible for this activity.…”
Section: Discussionmentioning
confidence: 99%
“…SbHE was prepared following the methodology described by González-Alamilla et al [ 27 ]. First, 1000 g of weeping willow leaves ( Salix babylonica ) were collected, washed, and dried in shade at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors [ 136 ] investigated the antibacterial effect of Salix babylonica L. hydroalcoholic extract against some pathogenic bacteria ( Escherichia coli , Staphylococcus aureus, and Listeria monocytogenes ). The authors showed antibacterial activity, mostly against Gram-positive bacteria Staphylococcus aureus and Listeria monocytogenes .…”
Section: Mechanisms Of Action Of Polyphenolsmentioning
confidence: 99%